2016
DOI: 10.1111/ncn3.12103
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel drug, zonisamide, in the modulation of oxidative stress in Parkinson's disease

Abstract: Background: Urinary 8-hydroxy-2 0 -deoxyguanosine is frequently used as an index of cytotoxicity, particularly for oxidative stress. Current research shows that urinary 8-hydroxy-2 0 -deoxyguanosine levels increase with age, disease duration and severity in patients with Parkinson's disease. In particular, a previous study reported that 8-hydroxy-2 0 -deoxyguanosine levels were increased in patients with hallucinations. Aim: Urinary 8-hydroxy-2 0 -deoxyguanosine levels were investigated as an indicator of clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…To reduce inter-/intra-rater variability, training was conducted prior to the trial start. A more detailed analysis of the effects of zonisamide on the following four motor symptoms [31] was also performed: tremor (items 20, 21), rigidity (item 22), bradykinesia (items [23][24][25][26]31), and postural instability/gait disturbance (PIGD) (items 29,30). For each individual motor symptom, patients with zero or missing values throughout the trial were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce inter-/intra-rater variability, training was conducted prior to the trial start. A more detailed analysis of the effects of zonisamide on the following four motor symptoms [31] was also performed: tremor (items 20, 21), rigidity (item 22), bradykinesia (items [23][24][25][26]31), and postural instability/gait disturbance (PIGD) (items 29,30). For each individual motor symptom, patients with zero or missing values throughout the trial were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed pharmacologic mechanisms responsible for the antiparkinsonian activity of zonisamide include both dopaminergic (activation of dopamine synthesis and release [21] and inhibition of monoamine oxidase-B [22]) and non-dopaminergic (blockade of sodium channels [23] and T-type calcium channels [24]) functions. In addition, neuroprotective effects of zonisamide have been reported [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to antioxidative action, ZNS scavenges free radicals of hydroxyl and nitric oxide [35] and can suppress nitric oxide synthase activity [36] and lipid peroxide formation [37]. 8-hydroxy-20-deoxyguanosine (8-OHdG) is a biomarker for oxidative stress, and urinary 8-OHdG levels were decreased in ZNS-treated PD patients [38]. These previous studies revealed that ZNS is a multifunctional and neuroprotective drug for several kinds of neuronal diseases [15][16][17][18][23][24][25][26][27][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Zonisamide later received its FDA approval as an adjuvant treatment for partial seizures in 2000. Over the years, the ameliorative effect of this drug in both partial and generalized seizures [2][3][4][5][6][7] as well as several other neurological disorders namely, psychotic conditions [8], Parkinson disease [9][10][11][12][13], neuropathic pain [14] and essential tremor [15] have been investigated. Although the precise mechanism of Zonisamide has not yet fully understood, blockage of voltagegated sodium channels and T-type calcium channels seems to be the principle route of action.…”
Section: Zonisamidementioning
confidence: 99%